Tinjauan Hukum Pidana Islam Terhadap Penambangan Pasir Ilegal Untuk Bahan Pembangunan Proyek Di Pasaman Barat - Ibnu Qodri, M.; Alfauza Marpaung, Zaid (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The sand mining activities taking place in West Pasaman, specifically in the Paku River area, Kinali Nagari, Kinali District, are unauthorized or illegal mining activities carried out by several parties. The consequences of this mining have led to environmental damage, prompting local residents to report the matter to the West Pasaman District Police for legal action. This study aims to examine Islamic criminal law related to illegal sand mining used for construction projects in West Pasaman. The method used in this research is empirical juridical research using primary and secondary data. Factors that contribute to illegal sand mining in the Paku River area, Kinali Nagari, Kinali District, West Pasaman Regency include economic needs, demand for building materials, lack of supervision and legal socialization on mining, and the difficulty of obtaining people's mining licenses (IPR) or special mining business permits (IUPK). The results of the study show that illegal mining is regulated under Law No. 3 of 2020, specifically in Articles 158 to 164. Unauthorized sand mining is regulated in Articles 158 to 164 of Law No. 4 of 2009. From the perspective of Islamic criminal law, illegal sand mining that causes environmental damage is considered a prohibited act (jarimah), as explained in Surah Al-Baqarah 205, which emphasizes that humans have a responsibility to manage and utilize natural resources wisely to achieve prosperity and to protect the environment in all contexts.